Computed Tomography And Ultrasound Guided Fine Needle Aspiration Cytology In The Diagnosis Of Intraabdominal And Pelvic Lesions: A Single Institutional Experience - Philipose, Cheryl Sarah; Amin, Ashima N; S, Jayaprakash C (Annals of Pathology and Laboratory Medicine, 2018)
Background: Fine needle aspiration cytology (FNAC) as an initial screening modality is an important interventional method. Technical advances in the method of radiology have it made it possible for many inaccessible lesions within the abdomen and pelvis to be safely sampled. Although FNA yields limited material, a positive diagnosis can contribute to the treatment, thus limiting the need for a core biopsy or 2 step surgical procedure. The procedure is relatively inexpensive and can also be done on an outpatient basis with minimal morbity to the patient. Methods: The present study is a retrospective study carried out from January 2012 to October 2014. All the patients in whom intra abdominal and pelvic lesions were detected clinically and by imaging modalities such as CT and USG, were included. The alcohol fixed (PAP) and air dried (MGG) smears of the selected cases were retrieved from archives and cytomorphological features were studied. Result: A total of 755 aspirations were carried out under image guidance, of which 208 aspirates (27.54%) included only intraabdominal and intrapelvic lesions. Majority of the patients in the study were males (51%). Total number of inflammatory lesions were 16 cases, benign lesions were 10 cases and malignant lesions were 164 cases. The most commonly encountered malignancy was metastasis to the liver. Conclusion: CT and USG guided FNAC is able to overcome various obstacles such as inaccessibility of deep seated intraabdominal lesions and is a valuable tool for yielding cellular smears.